Fusion imaging in preoperative assessment of extent of disease in patients with advanced ovarian cancer: feasibility and agreement with laparoscopic findings. (1st December 2021) - Moro, F.; Bertoldo, V.; Avesani, G.; Moruzzi, M. C.; Mascilini, F.; Bolomini, G.; Caliolo, G.; Esposito, R.; Moroni, R.; Zannoni, G. F.; Fagotti, A.; Manfredi, R.; et al.
ABSTRACT: Objectives: Fusion imaging is an emerging technique that combines real‐time ultrasound examination with images acquired previously using other modalities, such as computed tomography (CT), magnetic resonance imaging and positron emission tomography. The primary aim of this study was to evaluate the feasibility of fusion imaging in patients with suspicion of ovarian or peritoneal cancer. Secondary aims were: to compare the agreement of findings on fusion imaging, CT alone and ultrasound imaging alone with laparoscopic findings, in the assessment of extent of intra‐abdominal disease; and to evaluate the time required for the fusion imaging technique. Methods: Patients with clinical and/or radiographic suspicion of advanced ovarian or peritoneal cancer who were candidates for surgery were enrolled prospectively between December 2019 and September 2020. All patients underwent a CT scan and ultrasound and fusion imaging to evaluate the presence or absence of the following abdominal‐cancer features according to the laparoscopy‐based scoring model (predictive index value (PIV)): supracolic omental disease, visceral carcinomatosis on the liver, lesser omental carcinomatosis and/or visceral carcinomatosis on the lesser curvature of the stomach and/or spleen, involvement of the paracolic gutter(s) and/or anterior abdominal wall, involvement of the diaphragm and visceral carcinomatosis on the small and/or large bowel (regardless of rectosigmoid involvement). The feasibility of the fusion examination in these patients was evaluated. Agreement of each imaging method (ultrasound, CT and fusion imaging) with laparoscopy (considered as reference standard) was calculated using Cohen's kappa coefficient. Results: Fifty‐two patients were enrolled into the study. Fusion imaging was feasible in 51 (98%) of these patients (in one patient, it was not possible for technical reasons). Two patients were excluded because laparoscopy was not performed, leaving 49 women in the final analysis. Kappa values for CT, ultrasound and fusion imaging, using laparoscopy as the reference standard, in assessing the PIV parameters were, respectively: 0.781, 0.845 and 0.896 for the great omentum; 0.329, 0.608 and 0.847 for the liver surface; 0.472, 0.549 and 0.756 for the lesser omentum and/or stomach and/or spleen; 0.385, 0.588 and 0.795 for the paracolic gutter(s) and/or anterior abdominal wall; 0.385, 0.497 and 0.657 for the diaphragm; and 0.336, 0.410 and 0.469 for the bowel. The median time needed to perform the fusion examination was 20 (range, 10–40) min. Conclusion: Fusion of CT images and real‐time ultrasound imaging is feasible in patients with suspicion of ovarian or peritoneal cancer and improves the agreement with surgical findings when compared with ultrasound or CT scan alone. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Fusión de imágenes en la evaluación preoperatoria del grado de enfermedad en pacientes con cáncer de ovario avanzado: viabilidad y concordancia con los resultados laparoscópicos Objetivos: La fusión de imágenes es una técnica novedosa que combina el examen ecográfico en tiempo real con imágenes adquiridas previamente mediante otras modalidades, como la tomografía computarizada (TC), la resonancia magnética y la tomografía por emisión de positrones. El objetivo principal de este estudio fue evaluar la viabilidad de la fusión de imágenes en pacientes con indicios de cáncer de ovario o peritoneal. Los objetivos secundarios fueron: comparar la concordancia de los hallazgos en la fusión de imágenes, tanto de la TC por sí sola como de la imagen de ultrasonido por sí sola con los hallazgos laparoscópicos, en la evaluación del grado de enfermedad intraabdominal; y evaluar el tiempo requerido para la técnica de fusión de imágenes. Métodos: Se reclutó de forma prospectiva a pacientes con indicios clínicos y/o radiográficos de cáncer de ovario o peritoneal avanzado consideradas como candidatas a cirugía entre diciembre de 2019 y septiembre de 2020. Todas las pacientes fueron sometidas a una TC y una ecografía así como a la fusión de imágenes, con el fin de evaluar la presencia o ausencia de las siguientes características del cáncer abdominal según el modelo de puntuación por laparoscopia (valor del índice predictivo (PIV)): enfermedad epiploica supracólica; carcinomatosis visceral en el hígado; carcinomatosis epiploica menor y/o carcinomatosis visceral en la curvatura menor del estómago y/o del bazo; afectación de los surcos paracólicos y/o de la pared abdominal anterior; afectación del diafragma y carcinomatosis visceral en el intestino delgado y/o grueso (independientemente de la afectación del rectosigmoide). Se evaluó la viabilidad del examen de fusión en estas pacientes. Se calculó la concordancia de cada método de imagen (ecografía, TC y fusión de imágenes) con la laparoscopia (considerada como el estándar de referencia) mediante el coeficiente kappa de Cohen. Resultados: Se reclutaron 52 pacientes para el estudio. La fusión de imágenes fue viable para 51 (98%) de estas pacientes (a una paciente no fue posible por razones técnicas). Se excluyeron dos pacientes porque no se realizó la laparoscopia, lo que dejó a 49 mujeres para el análisis final. Los valores kappa para la TC, la ecografía y la fusión de imágenes, utilizando la laparoscopia como estándar de referencia, en la evaluación de los parámetros PIV fueron, respectivamente: 0, 781, 0, 845 y 0, 896 para el epiplón mayor; 0, 329, 0, 608 y 0, 847 para la superficie del hígado; 0, 472, 0, 549 y 0, 756 para el epiplón menor y/o el estómago y/o el bazo; 0, 385, 0, 588 y 0, 795 para los surcos paracólicos y/o la pared abdominal anterior; 0, 385, 0, 497 y 0, 657 para el diafragma; y 0, 336, 0, 410 y 0, 469 para el intestino. La mediana del tiempo necesario para realizar el examen de fusión fue de 20 minutos (rango, 10–40). Conclusión: La fusión de imágenes de TC y de ecografía en tiempo real es factible en pacientes con indicios de cáncer de ovario o peritoneal y mejora la concordancia con los hallazgos quirúrgicos, en comparación con la ecografía o la TC por separado. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 图像融合用于晚期卵巢癌患者病情程度的术前评估:可行性及与腹腔镜检查结果的一致性 目的: 图像融合是一种新兴技术，将实时超声检查与先前以其他医疗器械获得的图像相结合，如计算机断层扫描(CT)、磁共振成像和正电子发射计算机断层扫描。这项研究的主要目的是评估对疑似卵巢癌或腹膜癌患者使用图像融合的可行性。次要目的有:对比图像融合、单独CT检查和单独超声检查与腹腔镜检查结果的相同之处，对腹内疾病程度的评估，以及评估图像融合技术所需的时间。 方法: 临床和/或射线检测疑似晚期卵巢癌或腹膜癌的手术候选患者，在2019年12月至2020年9月之间预期参加。所有患者均进行了一次CT扫描、超声和图像融合来评估以下腹部肿瘤特征是否存在(依据基于腹腔镜检查的评分模型——预测指数值(PIV)):结肠上网膜疾病，肝脏上的内脏癌症，小网膜癌症和/或在胃小弯和/或脾脏上的内脏癌症，涉及肠旁沟和/或前腹壁，涉及隔膜和小肠和/或大肠上的内脏癌症(不论是否涉及直肠乙状结肠)。对这些患者进行了融合检查可行性的评估。每种影像学方法(超声、ct和图像融合)与腹腔镜检查(作为参考标准)的一致之处都采用科恩的Kappa系数(Cohen's kappa coefficient)进行计算。 结果: 本研究有52名患者参加。图像融合在51名(98%)患者中可行(对一名患者，由于技术原因不可能进行)。由于未进行腹腔镜检查，有两名患者被排除，剩下49名女性患者进入最终分析。用腹腔镜检查作为参考标准，为评估PIV参数，CT、超声和图像融合的Kappa值分别为:大网膜:0.781，0.845和0.896；肝被膜:0.329，0.608和0.847；小网膜和/或胃和/或脾脏:0.472、0.549和0.756；肠旁沟和/或前腹壁:0.385、0.588和0.795；隔膜:0.385、0.497和0.657；以及肠道:0.336、0.410和0.469。进行融合检查所需的平均时间为20分钟(范围:10‐40分钟)。 结论: 与单独进行超声或CT扫描相比，CT图像及实时超声影像融合对疑似卵巢癌或腹膜癌患者是可行的，而且改善与手术治疗发现的一致。© 2021年国际妇产科超声学会。